2009
DOI: 10.1051/0004-6361/200811357
|View full text |Cite
|
Sign up to set email alerts
|

Detection of very high energy radiation from HESS J1908+063 confirms the Milagro unidentified source MGRO J1908+06

Abstract: Aims. Detection of a γ-ray source above 300 GeV is reported, confirming the unidentified source MGRO J1908+06, discovered by the Milagro collaboration at a median energy of 20 TeV. Methods. The source was observed during 27 h as part of the extension of the HESS Galactic plane survey to longitudes >30• . Results. HESS J1908+063 is detected at a significance level of 10.9σ with an integral flux above 1 TeV of (3.76 ± 0.29 stat ± 0.75 sys ) × 10 −12 ph cm −2 s −1 , and a spectral photon index Γ = 2.10 ± 0.07 sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 26 publications
3
44
0
1
Order By: Relevance
“…The data were consistent both with a point source and with an extended source of diameter <2.6°. The Cherenkov telescope HESS confirmed the discovery with the detection of the extended .source HESS J1908+063 (Aharonian et al, 2009) at energies above 300 GeV, positionally consistent with the MILAGRO source. The extension of the source, evaluated assuming a symmetrical twodimensional Gaussian shape, was <Text=0.34°^Q,,j.…”
Section: Mgroj1908+06supporting
confidence: 64%
“…The data were consistent both with a point source and with an extended source of diameter <2.6°. The Cherenkov telescope HESS confirmed the discovery with the detection of the extended .source HESS J1908+063 (Aharonian et al, 2009) at energies above 300 GeV, positionally consistent with the MILAGRO source. The extension of the source, evaluated assuming a symmetrical twodimensional Gaussian shape, was <Text=0.34°^Q,,j.…”
Section: Mgroj1908+06supporting
confidence: 64%
“…Abdo et al (2010) found that this pulsar (yellow cross in Figure 6) lies in the extended emission seen also with the High Energy Stereoscopic System (HESS; Aharonian et al 2009) and the Very Energetic Radiation Imaging Telescope Array System (VERITAS; Ward 2008). They noted, however, that the association with G40.5-0.5 seems very unlikely as it would require an extremely high transverse velocity and should have resulted in a bow-shock shaped nebula near the pulsar which was not evident in their Chandra X-ray observations.…”
Section: Psr J1907+0631mentioning
confidence: 93%
“…[16,20,21], and the ARGO-YBJ experiment [22]. This source has been detected also by ACTs, like HESS [23], which finds a spectrum with no evidence of a cut-off for energies < 20 TeV. The HESS detector reports a flux systematically lower than the Milagro and ARGO-YBJ data.…”
Section: Mgro J1908+06mentioning
confidence: 95%